Effects of Additional Exercise Volume on Body Composition (Weight, Body Mass Index, and Fat Percentage) and Performance Metrics (Power, Strength, and Fatigue Index) in Adolescent Wrestlers - Kheirandish, Reza; Rahmani, Ahmad; Gorzi, Ali; Shaabani Ezdini, Ebrahim (Health Nexus, 2025)
This study investigated the effects of a structured two-week exercise intervention combining wrestling drills, resistance training, and high-intensity interval training (HIIT) on body composition and performance metrics in adolescent wrestlers aged 15-19 years. Twenty male wrestlers from Soltanieh city were divided into experimental and control groups. The experimental group underwent a structured exercise intervention including resistance training (once weekly at 50-55% 1RM), HIIT (four to five 35-meter sprints), and speed training (50-meter sprints), alongside regular wrestling drills. Body composition (weight, BMI, body fat percentage) and performance metrics (power, strength, fatigue index) were assessed pre- and post-intervention. Analysis of covariance revealed significant improvements in the experimental group for weight reduction (F(1,17)=8.24, p=0.007, η²=0.182), body fat percentage (F(1,17)=15.63, p